Ecobrick Workshop to Strengthen Plastic Waste Management Literacy among Primary and Lower Secondary Students - Sofyan Sofyan; A. Noer Chalifah Ramadhany; Ferdhiyadi Ferdhiyadi; Alwi Usra Usman (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Plastic waste remains a pressing environmental issue, particularly in areas with limited waste management infrastructure. This community engagement program aims to enhance environmental literacy and plastic waste management skills among students in primary and lower secondary education through an ecobrick workshop. Ecobrick—compacting non-biodegradable plastic waste into reused bottles—was selected as an educational tool due to its simplicity, practicality, and potential for reuse in building small-scale structures. The activities were conducted using a participatory approach involving demonstrations, hands-on practice, and education on plastic waste impacts, 3R principles, and sustainable waste management behaviors. The results indicate improved student understanding of environmental issues and increased ability to independently create ecobricks. Beyond promoting environmentally responsible behavior, the ecobricks produced can be collectively utilized by schools or community groups for simple infrastructure projects. This program demonstrates that practice-oriented environmental education can effectively foster sustainable plastic waste management culture among young learners.